Apego m??e-beb?? no sistema prisional - Oliveira, Lesly Guimar??es Vicenzi de (2017)
The doctoral thesis aimed at presenting the development of the mother-baby attachment in prison anchored on the care provided by mothers, intertwined by their history and the impact of the closer social relations, namely: other women inmates, visitors and prison officers. Despite the growing increase in the Brazilian female prison population, there is little research interested in the relation to the Mother-Baby Attachment within the Prison System. Bolwby's theory of attachment was used as the theoretical foundation. To understand the field of study, the realated literature was reviewed on: development and attachment of young children; Mother-baby attachment in prison; and interventional proposals related to the development of mother-child attachment. Four women imprisoned in the Federal Disctrict (DF) Women's Penitentiary were followed up for a little more than a year, from their pregnancy to the subsequent delivery of the babies from the prison environment. The following were applied: Adult Attachment Scale-R (AAS-R); Maternal-Fetal Attachment Scale (MFAS); Factorial scale of neuroticism (EFN); Perceived Maternal Parenting Self- Efficacy (PMP SE); Edinburgh Postpartum Depression Scale (EPDS). Five semi-structured interviews were carried out and a systematic checklist of baby development (Checklist) was used, as well as the reading of court records and the field diary. The results showed that the practice of child-care is anchored on rules passed down family generations, but in the Prison System they have impacts: both positive when their rules cover in a certain way matters related to mothering (orientations received) and the withdrawal of social vulnerability; As well as negative in what affects the way in which the mother's monitoring of her baby is exercised, which generates anxiety, insecurity and consequently the possibility of the development of insecure attachment in the baby. It is proposed to know and ponder the various interventions and results found in the area of maternal attachment and consequent development of the child to implement interventions in the prison system. In addition to making changes in the way to structure activities for women who live with their babies in jail with a view to enabling them to stay with their babies in the longer term which may favor safe attachment.